Experimental and numerical analysis of deep drawing process - Mohamad Nazrin Kooy, Mohd Daniel Kooy (2010)
One of the most common outcomes in deep drawing process is earing, or the formation of uneven height at the top rim of a drawn part due to the material anisotropy. The present study involves experimental and numerical studies of earing formation in deep drawing process. The main objective of the present study is to determine the accuracy of Hill’s 1948 and Barlat 1991 yield criteria in predicting earing using only uniaxial tensile test data for FCC materials. The second objective is to investigate the effects of blank diameter and blank holder force (BHF) on earing behavior. A deep drawing die for cylindrical cup has been designed for the present study. For the experiments, two groups of blanks made from aluminum alloy AA1100 and commercially pure copper were drawn using two sets of BHF. The earing profiles were measured at every increment of 5 degrees from original sheet metal rolling direction, which were then symmetrized and normalized for comparison. For the finite element analysis, the process is modeled as a 3 dimensional, quarter-model in MSC.PATRAN with MSC.MARC as nonlinear implicit solver. Results showed that using only uniaxial tensile test data, Hill’s 1948 yield criterion was able to accurately predict earing behavior for aluminum. However, Hill’s 1948 criterion did not accurately predict earing for copper due to simplifying assumptions used in the FEA. The yield stresses and plastic flow curve should be averaged for all orientations for materials with high angular yield stress difference such as copper. Barlat 1991 criterion was observed to be unable to predict earing behavior for both metals due to its dependency on yield stresses input only. It was also observed that percentage earing increases with increasing blank diameter. BHF did not affect earing behavior directly, but insufficient BHF were observed to cause wrinkling, resulted in irregular height profiles. The results concluded that using only uniaxial tensile test data, Hill’s 1948 criterion performed well in predicting earing profile for aluminum alloys, which is significant to accurately predict earing behavior for aluminum alloys with yield criterion approach using only uniaxial tensile test data in engineering applications.